2021
DOI: 10.22470/pemj.2021.00269
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tetanus

Abstract: Neonatal tetanus, also known as tetanus neonatorum, occurs in young infants of inadequately immunized mothers. It is a kind of generalized tetanus that is exhibited mainly by prevention of the release of the inhibitory neurotransmitters (i.e., disinhibition) and is initiated by tetanospasmin, an exotoxin created by Clostridium tetani. Contamination of the umbilical cord stump is the main cause. The typical, early manifestations are weakness and lack of ability to suck, continuing within hours to trismus, risus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Low birthweight, short incubation period, short period of onset, delay in seeking medical assistance, presence of comorbidities, dose of tetanus immunoglobulin 250 IU, and unclear entry site of infection determined mortality in these patients. Gender and delivery location were not related with an increased risk of mortality [12][13] . The leading causes of pre-discharge neonatal mortality were respiratory and cardiovascular diseases (43%) and low birthweight and prematurity (33%).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Low birthweight, short incubation period, short period of onset, delay in seeking medical assistance, presence of comorbidities, dose of tetanus immunoglobulin 250 IU, and unclear entry site of infection determined mortality in these patients. Gender and delivery location were not related with an increased risk of mortality [12][13] . The leading causes of pre-discharge neonatal mortality were respiratory and cardiovascular diseases (43%) and low birthweight and prematurity (33%).…”
Section: Discussionmentioning
confidence: 85%
“…The findings revealed that a significantly high number of women were not immunized against the tetanus infection (p<0.05), followed by the immunized mothers with a single and double shots of the vaccine administration with the frequency of 55. 13,38.91 and 5.94%, respectively (Figure 3). The fetal umbilical cord was also one of the high risk factor due to the creation of deep wound post-partum with the potential risk of entrance of Clostridium bacteria.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Pada saat pemotongan ari-ari janin bila dilakukan menggunakan alat yang tidak steril, selain itu pencegahan pula bagi neonatusnya. Oleh karena bakteri Clostridium tetani akan menyebar melalui peredaran darah air-ari janin ke seluruh tubuh (Brook, 2021).…”
Section: Pendahuluanunclassified